The contribution of forests and trees to sustainable diets - Vinceti, B.; Termote, Céline; Ickowitz, A.; Powell, B.; Kehlenbeck, K.; Hunter, D. (MDPI, 2013)
With the growing demands from a population expected to reach 9 billion people by 2050, it is unclear how our current global food system will meet future food needs. Ensuring that all people have access to adequate and nutritious food produced in an environmentally and socio-culturally sustainable manner is one of the greatest challenges of our time. “Sustainable diets” have been proposed as a multidimensional framework to address the need for nutritious and adequate food in the context of the many challenges facing the world today: reducing poverty and hunger, improving environmental health, enhancing human well-being and health, and strengthening local food networks, sustainable livelihoods and cultural heritage. This paper examines the contribution of forests and trees to sustainable diets, covering among others, nutritional, cultural, environmental and provisioning aspects. The literature reviewed highlight major opportunities to strengthen the contribution of forest and tree foods to sustainable diets. However, several constraints need to be removed. They relate to: cultural aspects, sustainable use of non-wood forest products, organization of forest food provisioning, limited knowledge of forest food composition, challenges in adapting management of forests and trees to account for forest foods, and in integrating forest biodiversity into complex landscapes managed for multiple benefits. Finally, the paper identifies research gaps and makes recommendations to enhance the contribution of forest foods to sustainable diets through increased awareness and better integration of information and knowledge on nutritious forest foods into national nutrition strategies and programs.